2010
DOI: 10.1074/jbc.c109.071225
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Induction by 1,25-Dihydroxyvitamin D3 of the NOD2/CARD15-Defensin β2 Innate Immune Pathway Defective in Crohn Disease

Abstract: Importantly, this synergistic response was also seen in macrophages from a donor wild type for NOD2 but was absent in macrophages from patients with Crohn disease homozygous for non-functional NOD2 variants. These studies provide strong molecular links between vitamin D deficiency and the genetics of Crohn disease, a chronic incurable inflammatory bowel condition, as Crohn's pathogenesis is associated with attenuated NOD2 or DEFB2/HBD2 function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
290
3
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(306 citation statements)
references
References 38 publications
7
290
3
6
Order By: Relevance
“…In addition, vitamin D deficiency [174], as well as active and passive tobacco smoking [13,175], air pollution [176] or improved domestic hygiene and sanitation [177] are additional factors that may modify the homeostasis of the intestinal mucosa. The observations, that IBD is common in Western countries, while uncommon in less developed areas, raised the intriguing hypothesis that improved hygiene and the consequent loss of routine exposure to parasitic worms (helminths) may play an important role in the pathomechanism of IBD [178].…”
Section: Environmental Factorsmentioning
confidence: 99%
“…In addition, vitamin D deficiency [174], as well as active and passive tobacco smoking [13,175], air pollution [176] or improved domestic hygiene and sanitation [177] are additional factors that may modify the homeostasis of the intestinal mucosa. The observations, that IBD is common in Western countries, while uncommon in less developed areas, raised the intriguing hypothesis that improved hygiene and the consequent loss of routine exposure to parasitic worms (helminths) may play an important role in the pathomechanism of IBD [178].…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Indeed, Kanchwala et al showed that patients with sarcoidosis expressed the antimicrobial peptide cathelicidin less than healthy subjects, and that the sickest sarcoidosis patients expressed it least of all. 51 In patients with Crohn's disease, Wang et al also demonstrated a decline in levels of cathelicidin, 52 while Wiken et al showed reduced TLR2 mRNA expression in patients with Lofgren's syndrome. 53 After a certain level of dysbiosis has occurred, people may well reach the point where they can be diagnosed with an autoimmune/inflammatory condition.…”
Section: Successive Infectionmentioning
confidence: 99%
“…IL-1β has been implicated in the pathogenesis of human cerebral malaria and severe malaria anemia [86][87]. However, calcitriol strongly stimulates NOD2 expression in differentiated human THP-1 macrophage-like cells, primary human monocytes and keratinocytes [88], and boosts autophagy by enhancing NOD2 function [89]. The calcitriol-stimulated NOD2 function may contribute to host resistance to a variety of infectious challenges.…”
Section: The Genomic Factors Associated With Vitamin D In Malariamentioning
confidence: 99%